The politics of statelessness, refugeehood, and humanitarianism of the Rohingyas - Kaveri,; Rajan, S. Irudaya (Frontiers in Human Dynamics, 2023)
Undoubtedly, the Rohingyas crisis has been one of the most talking points in the last few years. The political exclusion and persecution revolve around the fault lines of modern nation-states built along the ethno-religious lines, making them the most persecuted minority in the world. Especially, post-global denunciation of the military crackdown in August 2017 and the United Nations accusing the country of ‘ethnic cleansing and genocide’ led to the massive exodus of people to the neighbouring countries and beyond. Yet, the existing political and protection space for stateless Rohingya refugees is extremely volatile due to the absence of legal mechanisms, un-documentedness, and rising security concerns globally often criminalising them as illegal migrants/immigrants or threats to national security. Forcing them to live under continuous threat of detention, deportation, and forced relocation further tarnishes their identity between the man and the citizen, dumping them into a socio-legal limbo. Based on the ethnographic inquiry conducted among stateless Rohingya refugees living in semi-urban ghettoes of India- Delhi, Mewat, Hyderabad and Jammu, the article looks into the historical and political trajectory of exclusion, resistance, and counter-resilience of stateless Rohingya refugees fleeing persecution in Myanmar along exploring their refracted and displaced realities and complexities of ‘everyday life’ in asylum and protracted refugeeness in India. And, the responses made by national and international agencies to the crisis. In doing so, it provides a grim insight into the inadequate, inconsistent and highly uncoordinated national and international response on care and protection and aid politics that has contributed to the collective failure in addressing the crisis. Thereby, the paper attempts to bring forth the wider debate upon issues of state and statehood, rights and humanitarianism within the nation-state paradigm.